Deteksi Dini Atresia Bilier dan Tatalaksana Kolangitis Pasca Hepatoportoenterostomi di Fasilitas Terbatas: Laporan Kasus - Zahra Qori Azizza; Mohammad Taufik Perwira Wicaksono (CV. Jasa Sukses Abadi, 2026)
Biliary atresia is the most common cause of extrahepatic cholestasis in infants, with an incidence of approximately 1 in 8,000–18,000 live births. Delayed diagnosis can decrease the success rate of hepatoportoenterostomy and increase the risk of cirrhosis and end-stage liver failure. Early detection of biliary atresia can be achieved through the identification of three characteristic signs: pale or tarry stools, elevated gamma-glutamyltransferase (GGT) levels >250 IU/L, and ultrasound findings suggestive of biliary atresia. Hepatoportoenterostomy is the definitive treatment to restore bile flow from the remaining patent intrahepatic bile ducts to the intestinal tract. However, this procedure often has complications, including cholangitis due to ascending bacterial infection through the hepatoportoenterostomy anastomosis. This article reports a case of a male infant who began experiencing persistent jaundice and tarry stools at two weeks of age. At 40 days of age, an increase in direct bilirubin and a GGT level of 606 IU/L were found, suggesting biliary atresia, although other differential diagnoses still needed to be ruled out. Limited diagnostic facilities in the area required referral for intraoperative cholangiography, which confirmed the diagnosis of biliary atresia and was followed by hepatoportoenterostomy. At five months of age, the patient returned with fever, jaundice, and tarry stools, suggesting postoperative cholangitis. Initial antibiotic therapy did not improve clinically, but the patient's condition improved after seven days of meropenem. This case highlights the importance of early detection of biliary atresia, awareness of post-hepatoportoenterostomy cholangitis, and the challenges of diagnosis and management in resource-limited healthcare facilities.